Coordination polymers of manganese(II), cobalt(II), nickel(II) and cadmium(II) decorated with rigid pyrazine-2, 3-dicarboxylic acid linker: Synthesis, structural diversity, DFT study and magneto-luminescence properties. (1st September 2020) - Sen, Charanjeet; Kumar, Manesh; ul Nisa, Zaib; Akhter Ashashi, Nargis; Frontera, Antonio; Chandra Sahoo, Subash; Nawaz Sheikh, Haq
Graphical abstract: In this contribution, solvothermal self-assembly of four new coordination polymers of transition metals decorated with pyrazine-2, 3-dicarboxylic acid, having one-dimensional [Mn(II), Co(II) and Ni(II)] and three-dimensional [only Cd(II)] architectures, is reported. Highlights: Four new CPs of Mn(II), Co(II), Ni(II) and Cd(II) decorated with Pyrazine-2, 3-dicarboxylic acid have been reported. The multitopic H2 Pyzdc linker exhibits three different coordination modes. Magnetic studies on CPs 1 –3 have been performed under low temperature. Ligand based photoluminescence of CP 4 has been studied. A DFT investigation reveals an interesting π-hole interaction involving the coordinated carboxylate group. Abstract: Single crystal diffraction analysis shows the formation of four new coordination polymers (CPs), viz . {[Mn(Pyzdc)(H2 O)2 ]·2H2 O}n (1 ), [Co(Pyzdc)(H2 O)2 ]n (2 ), [Ni(Pyzdc)(H2 O)2 ]n (3 ) and [Cd(Pyzdc)]n (4 ) (where Pyzdc 2− stands for the fully-deprotonated pyrazine-2, 3-dicarboxylic acid), by the solvothermal self-assembly of the four titled metal(II) nitrates with rigid pyrazine-2, 3-dicarboxylic acid. CP 1 crystallizes in the monoclinic P 21 / c space group, whereas CPs 2, 3 and 4 have orthorhombic Pcca, Pcca and Pnna space groups respectively. CPs 1 –4 consist of dinuclear secondary building units (SBUs) [Mn2 O10 N2 (1 ), M2 O8 N4 (where M=Co (2 ) and Ni (3 )) and Cd2 O6 N4 (4 )]. In CPs 1 –3 (Mn, Co and Ni), covalent interactions foster into one-dimensional structures, whereas CP 4 (Cd) exhibits a three-dimensional architecture. The Pyzdc linker exhibits three different coordination modes (μ3 -κO:κO:κO:κN for CP 1, μ2 -κO:κO:κN:κN for CPs 2 and 3, and μ4 -κO, O:κO, O:κN:κN for CP 4 ). DFT calculations reveal that in one compound (CP 1 ), interesting π-hole interactions exist, which have been evaluated energetically (at the PBE1PBE-D3/def2-TZVP level of theory) and characterized using the quantum theory of "atoms-in-molecules" (QTAIM). Magnetic studies reveal that the Weiss constant, based on the equation χm  = C/(T−θ), is negative (θ = −34.37, −50.46 and −37.09 K for CPs 1, 2 and 3 respectively). This suggests weak antiferromagnetic interactions between adjacent M(II) centers. Lastly, the ligand based photoluminescence of CP 4 has been explored.